Gray markets: past, present, and future. Issue 1 (1st January 2016) - Berman, Barry; Dong, Meichen
Abstract : This article conducts a literature review on three gray market areas: strategy, legal issues, and consumer behavior. Previous gray market strategy-based articles do not discuss the impact of the Web on gray market activity, limit their analysis to international gray markets, and do not identify situations where gray market activity is profitable for a manufacturer and its authorized resellers. Like the strategy-based articles, the legal issue-based articles confine their discussion to international gray markets. A current US Supreme Court case that expands the potential for gray market activity is discussed. The third research stream focuses on the impact of brand image and brand equity and the relationship of perceived risk and gray market acceptance by consumers. The authors develop an overall strategy for dealing with gray market activity based on balancing positive and negative issues. In some cases, it is prudent for manufacturers and resellers to view gray markets as an alternative strategy to private labels, second-tier brands, or fighting brands. In other instances, firms need to explore supply- and demand-based strategies to deter gray market activity. Alternative organization formats for gray market surveillance and control are discussed. Difficulties associated with conducting gray market research as well as directions for future research in gray markets are covered.